2021
DOI: 10.1007/s13178-020-00531-0
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Attitudes of Men Towards Sperm Donation: Whom to Donate and Why?

Abstract: Background The widespread access to medically assisted reproduction (MAR) techniques for all women, regardless of any infertility diagnosis, has led to an increased, but as yet unmet, demand for sperm donors in Portugal. For this study, we deployed an online survey to explore men's motivations for donating and their attitudes toward anonymity and donating for specific groups. Method The study's sample comprised men who were eligible to donate sperm (N = 282). The relationships between these factors and partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Interestingly, although the desire to help others build a family was highly rated, participants expressed very low scores regarding their willingness to familiarize with recipients and offspring. These findings are compatible with various previous reports which emphasized the combination of altruism and anonymity [ 13 , 28 ]. We assume that participants age and marital status (single) may have strong impact on these preferences.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, although the desire to help others build a family was highly rated, participants expressed very low scores regarding their willingness to familiarize with recipients and offspring. These findings are compatible with various previous reports which emphasized the combination of altruism and anonymity [ 13 , 28 ]. We assume that participants age and marital status (single) may have strong impact on these preferences.…”
Section: Discussionsupporting
confidence: 93%
“…The argument of this study that 'personal opinions and emotions may lead to different perspectives' may also be valid in our findings. Similar to our study, the study of Areias (2020) on the attitude and motivation towards sperm donation in Portugal, where gamete donation is legally allowed, (Fertility and Sterility, 2007) showed that participants who attach more importance to religious values were less motivated to help someone have a child and less willing to donate to all types of recipients. In line with our findings, in Ogunbode and Obajimi's (2020) study on students in Nigeria, more than half of the participants (54.9%) view gamete donation positively.…”
Section: Discussionsupporting
confidence: 87%
“…These results may be explained by reference to the prevailing familistic values held in Portugal and Israel compared to the more individualistic values adhered to in the UK (Birenbaum-Carmeli, 2016;Hofstede, 2011;Leal et al, 2019). Furthermore, notwithstanding the less favorable parenthood laws in Israel than in either Portugal or the UK (Areias et al, 2021;Costa & Shenkman, 2020;HFEA, 2008;Shenkman, 2021) or the more negative social climate towards LGB individuals in Portugal and Israel than in the UK (Flores, 2019) our findings indicate that sexual minority individuals might be more protected from stigma upon parenthood in the familistic societies, such as Portugal and Israel, than in individualistic societies, such as the UK (Leal et al, 2019;Shenkman et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…In 2016, Portuguese law extended publicly funded ART to all women, regardless of their marital status, sexual orientation, or any infertility diagnosis. However, surrogacy is not possible in Portugal neither for same-gender nor for differentgender couples (Areias et al, 2021).…”
Section: Sociolegal Restrictions and Parenthood: Heteronormativy And ...mentioning
confidence: 99%